RARE EARTH ELEMENTS IN TURKİYE: RESERVES, NATIONAL INTERESTS, AND INTERNATIONAL IMPLICATIONS - Cora, Ali Nazmi (TURAN : stratejik arastirmalar merkezi, 2025)
This study explores Türkiye’s rare earth element (REE) reserves and their multifaceted implications for national development and global geopolitics. With a global shift towards renewable energy and advanced technologies, REEs—particularly heavy elements like dysprosium and terbium—have gained strategic importance. Türkiye holds considerable potential with over 4.4 million tons of rare earth oxides, positioning itself as a potential supplier to Europe and the Middle East. The paper examines the geological distribution, extraction techniques, and market dynamics shaping Türkiye’s REE sector. Despite rich reserves, limitations in processing infrastructure, policy ambiguity, and environmental concerns hinder development. The study discusses the strategic importance of REEs for Türkiye’s political, military, and economic security, alongside the challenges of aligning national interests with sustainable resource management. The international landscape is also addressed, analyzing Türkiye’s role within global supply chains dominated by China, and identifying emerging diplomatic and trade strategies. Technological innovations in extraction and recycling are reviewed, along with Türkiye’s legislative framework and regulatory efforts aimed at fostering a secure and environmentally responsible REE sector. The paper concludes that Türkiye’s future as a key REE player depends on balancing national interests with international collaboration, institutional reform, and technological investment. Türkiye’s strategic geography, combined with rising demand for non-Chinese REE sources, gives it a unique opportunity to become a central actor in global energy and technology transitions.